Tinjauan Praktis Tentang Resolusi Konflik Berdasarkan Filemon 1:1-25 - Junio Richson Sirait; Muner Daliman; Hestyn Natal Istinatun; Sri Wahyuni (Jayapangus Press, 2022)
In general, researchers only focus on taking a practical approach to Paul trying to reconcile Philemon with Onesimus. Onesimus is a slave who has run away from his master, Philemon. Conflict resolution in Paul's letter to Philemon has not yet been researched. The purpose of this research is to find conflict resolution based on Philemon 1:1-25. The method used in this research is qualitative with a literature study approach. The result of the research on conflict resolution in Philemon 1:1-25 is that reconciliation must be realized based on the ties of brotherhood obtained from God's Ownership.